2016
DOI: 10.1002/mdc3.12323
|View full text |Cite
|
Sign up to set email alerts
|

Focal Muscle Vibration Improves Gait in Parkinson's Disease: A Pilot Randomized, Controlled Trial

Abstract: Background In Parkinson's disease (PD), gait disorders lead to increased risk of falls and patients' reduced participation and independence. Several observations suggest that a single session of focal muscle vibration (fMV) applied to trunk or lower limb muscles during gait may improve several gait variables in patients with PD. The possible long‐term beneficial effects of repetitive sessions of fMV (r‐fMV) on gait of patients with PD have been investigated. Methods A randomized, controlled trial study has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…The results of this study demonstrated that a four-week intervention of FMV can enhance the spatiotemporal parameters of gait, similar to studies reported for individuals with Parkinson’s disease (PD) and multiple sclerosis (MS) [ 38 , 39 ]. Camerota et al [ 38 ] found that after three consecutive days of one 60-min session of FMV per day, patients with PD had increased gait speed, stride length, and step length.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of this study demonstrated that a four-week intervention of FMV can enhance the spatiotemporal parameters of gait, similar to studies reported for individuals with Parkinson’s disease (PD) and multiple sclerosis (MS) [ 38 , 39 ]. Camerota et al [ 38 ] found that after three consecutive days of one 60-min session of FMV per day, patients with PD had increased gait speed, stride length, and step length.…”
Section: Discussionsupporting
confidence: 86%
“…The results of this study demonstrated that a four-week intervention of FMV can enhance the spatiotemporal parameters of gait, similar to studies reported for individuals with Parkinson’s disease (PD) and multiple sclerosis (MS) [ 38 , 39 ]. Camerota et al [ 38 ] found that after three consecutive days of one 60-min session of FMV per day, patients with PD had increased gait speed, stride length, and step length. Camerota et al [ 39 ] also showed that after three consecutive days of one 60-min session of FMV per day patients with MS had significant improvement in gait speed, double limb support, step length, stride length, and cadence.…”
Section: Discussionsupporting
confidence: 86%
“…Another relevant point concerns the putative physiological mechanisms responsible for the beneficial effect induced by vibration protocols. Several studies in animals and in humans have demonstrated that experimental modulation of proprioceptive inputs to the CNS can re-shape cortical mapping in the sensorimotor region, owing to use-dependent plasticity processes [70][71][72][73]. For instance, limb immobilization can deteriorate cortical motor representation of the target body region, reduce cortical excitability, and degrade motor learning [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…135 In addition, interventions that act mainly on the proprioceptive system, such as vibration to lower extremity or trunk muscles, may improve gait in PD. 13,[136][137][138][139] Tremor Intention tremor may decrease if patients execute a goal-directed movement based on previous knowledge of target position, instead of relying on visual feedback. 21,22,140 This may be useful to reduce tremor in activities that do not critically depend on online visual feedback, for example, shirt buttoning, brushing teeth, or stirring while cooking.…”
Section: Interventions That May Improve Functioning In Everyday Situamentioning
confidence: 99%
“…In addition, interventions that act mainly on the proprioceptive system, such as vibration to lower extremity or trunk muscles, may improve gait in PD 13,136‐139 …”
Section: Clinical Relevance Of Movement Disorders Variabilitymentioning
confidence: 99%